KEWENANGAN PEMERINTAH DAERAH DALAM PENGELOLAAN SDA PADA OTONOMI DAERAH - Said Abdullah (Jurnal LEX SPECIALIS, 2012)
Abstract The basic concept of regional autonomy is to give the authority to plan and implement the development of their respective regions in accordance with what they want and they need, and the central government will assist and maintain the activities that can not be implemented in areas such as monetary problems, development roads between cities and provinces, as well as maintenance of irrigation systems across various regions. Implementation of Regional Autonomy implemented by providing a broad powers, real and accountable to the Regional embodied proportionally with the setting, distribution and utilization of natural resources. Key Note : Management of Natural Resources